Vitamin D Alleviates Osteoarthritis Progression by Targeting Cartilage and Subchondral Bone via Myd88-TAK1-ERK Axis Suppression - Gao X; Min Y; Lin R; Liang D; Zhang M; Xiao Q; Lu Y; Zhang F; Xu B; Liu Y (Drug Design, Development and Therapy, 2025)
Xiang Gao,1,2,* Yalin Min,1,3,* Rui Lin,1,* Dahong Liang,1,3 Min Zhang,1,3 Qixian Xiao,1 Yan Lu,2 Fucheng Zhang,1 Bilian Xu,3,4 Yanzhi Liu1,4 1Key Laboratory of Traditional Chinese Medicine for the Prevention and Treatment of Infectious Diseases, Zhanjiang Central Hospital, Guangdong Medical University, Zhanjiang City, Guangdong Province, 524045, People’s Republic of China; 2Stem Cell Research and Cellular Therapy Center, The Affiliated Hospital of Guangdong Medical University, Zhanjiang City, Guangdong Province, 524001, People’s Republic of China; 3Marine Medical Research Institute of Zhanjiang, School of Ocean and Tropical Medicine, Guangdong Medical University, Zhanjiang City, Guangdong Province, 524023, People’s Republic of China; 4School of Pharmacy, Guangdong Medical University, Zhanjiang City, Guangdong Province, 524023, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanzhi Liu, Key Laboratory of Traditional Chinese Medicine for the Prevention and Treatment of Infectious Diseases, Zhanjiang Central Hospital, Guangdong Medical University, No. 236, Yuanzhu Road, Chikan Disctrict, Zhanjiang, 524045, People’s Republic of China, Email liuyanzhi02@163.com Bilian Xu, Marine Medical Research Institute of Zhanjiang, School of Ocean and Tropical Medicine, Guangdong Medical University, No. 2 Wenmingdong Road, Xiashan District, Zhanjiang, 524023, People’s Republic of China, Email xubilianq@126.comBackground: Osteoarthritis (OA) causes irreversible joint damage, but current treatments fail to fully address its complex pathology. Emerging evidence suggests subchondral bone metabolic dysfunction may initiate OA. While vitamin D (VitD) is well-established for bone metabolism regulation in osteoporosis, its therapeutic potential in OA remains unclear despite observational studies suggesting protective effects. Our integrated in vivo/in vitro study demonstrates VitD’s dual chondroprotective and osteogenic actions in OA.Methods: Sprague-Dawley rats (n=24) were divided into three groups: sham operation (Sham), OA model (OA), and OA+VitD treatment, with 8 rats in each group. Oral cholecalciferol (2.34 μg/kg/day) was administered for 6 weeks post-Monosodium iodoacetate (MIA) induction. The therapeutic potential of vitamin D was evaluated through a series of in vivo experiments. Human chondrocyte C28 cells were pretreated with TNFα (1ng/mL) to model inflammatory injury, followed by 1,25(OH)2 D3 (10− 2 μM) exposure for 72 hours to assess the VitD’s effects of chondrogenesis and further investigate its underlying mechanism.Results: In OA rats, VitD suppressed femoral cartilage degradation (evidenced by 567.76% increased cartilage area, and 39.13% decreased Osteoarthritis Cartilage Histopathology (OACH) score and enhanced subchondral bone mass (61.81% higher BV/TV). At the molecular level, VitD downregulated the expression of cartilage matrix metalloproteinase 13 (MMP13), with a reduction of 74.72% compared to OA group. Additionally, VitD inhibit inflammatory signaling pathways, particularly through the MyD88-TAK1-ERK axis in chondrocytes, and decrease serum IL-6 level. Mechanistic validation of these findings was demonstrated by protein expression reduction of Myd88 (31.22%), phospho-ERK1/2 (66.11%), AP-1 (61.43%) and NFκB (34.36%) compared to OA group. In vitro, VitD also rescued ethanol-induced C28 cell viability loss while significantly upregulating cartilage anabolic markers.Conclusion: These findings establish VitD as a multimodal OA therapeutic agent targeting both cartilage catabolism and subchondral bone remodeling through Myd88-TAK1-ERK axis. Keywords: vitamin D, bone, cartilage, osteoarthritis, rat